# Find the derivative of the following: - \[y={{2}^{x}}-3{{e}^{x}}-{{4}^{x}}\]

Last updated date: 30th Mar 2023

•

Total views: 309.6k

•

Views today: 8.87k

Answer

Verified

309.6k+ views

Hint: Use basic formulae for derivative of \[{{a}^{x}},{{x}^{a}}\And {{e}^{x}}\].

We have expression/function

\[y={{2}^{x}}-3{{e}^{x}}-{{4}^{x}}-(1)\]

Now, let us differentiate the given function as,

\[\dfrac{dy}{dx}=\dfrac{d}{dx}\left( {{2}^{x}}-3{{e}^{x}}-{{4}^{x}} \right)\]

One important rule should be applied here as stated below:

If we have $n$ functions ${{f}_{1}}(x),{{f}_{2}}(x),{{f}_{3}}(x)......{{f}_{n}}(x)$ and ${{\lambda }_{1}},{{\lambda }_{2}},{{\lambda }_{3}}......{{\lambda }_{n}}$ are constants in function $'y'$ as written below:

$y={{\lambda }_{1}}{{f}_{1}}(x)+{{\lambda }_{2}}{{f}_{2}}(x)+{{\lambda }_{3}}{{f}_{3}}(x)+......+{{\lambda }_{n}}{{f}_{n}}(x)$.

Now, if we differentiate the above given function $y$ , then we will get

$\begin{align}

& \dfrac{dy}{dx}=\dfrac{d}{dx}\left[ {{\lambda }_{1}}{{f}_{1}}(x)+{{\lambda }_{2}}{{f}_{2}}(x)+{{\lambda }_{3}}{{f}_{3}}(x)+......+{{\lambda }_{n}}{{f}_{n}}(x) \right] \\

& \dfrac{dy}{dx}=\dfrac{d}{dx}\left[ {{\lambda }_{1}}{{f}_{1}}(x) \right]+\dfrac{d}{dx}\left[ {{\lambda }_{2}}{{f}_{2}}(x) \right]+\dfrac{d}{dx}\left[ {{\lambda }_{3}}{{f}_{3}}(x) \right]+....+\dfrac{d}{dx}\left[ {{\lambda }_{n}}{{f}_{n}}(x) \right] \\

& \dfrac{dy}{dx}={{\lambda }_{1}}\dfrac{d}{dx}\left[ {{f}_{1}}(x) \right]+{{\lambda }_{2}}\dfrac{d}{dx}\left[ {{f}_{2}}(x) \right]+{{\lambda }_{3}}\dfrac{d}{dx}\left[ {{f}_{3}}(x) \right]+....+{{\lambda }_{n}}\dfrac{d}{dx}\left[ {{f}_{n}}(x) \right]........(2) \\

\end{align}$

So if functions are written in summation, then we can differentiate them individually. Using the above property in equation (1) as follows:

\[\begin{align}

& \dfrac{dy}{dx}=\dfrac{d}{dx}({{2}^{x}}-3{{e}^{x}}-{{4}^{x}}) \\

& \dfrac{d}{dx}=\dfrac{d}{dx}({{2}^{x}})-\dfrac{d}{dx}(3{{e}^{x}})-\dfrac{d}{dx}({{4}^{x}}) \\

\end{align}\]

Here, we can observe that ${{2}^{x}}$ is of type (Constant)function or ${{(\lambda )}^{f(x)}}$\ . So, we have formula for it as,

$\dfrac{d}{dx}({{a}^{x}})={{a}^{x}}\ln a$

Hence,

$\dfrac{d}{dx}({{2}^{x}})={{2}^{x}}\ln 2.........(4)$

Now, ${{e}^{x}}$ is exponential function and derivative of it is given as,

$\dfrac{d}{dx}({{e}^{x}})={{e}^{x}}........(5)$

Similarly, $\dfrac{d}{dx}({{4}^{x}})$ can be calculated by $\dfrac{d}{dx}({{a}^{x}})={{a}^{x}}\ln a$ formula as,

$\dfrac{d}{dx}({{4}^{x}})={{4}^{x}}\ln 4.........(6)$

Putting the values of equation (4), (5) and (6) in equation (3) for calculating,

\[\dfrac{dy}{dx}={{2}^{x}}\ln 2-3{{e}^{x}}-{{4}^{x}}\ln 4\]

Note: Student need to very clear with the functions like ${{a}^{x}},{{x}^{a}},{{x}^{x}},{{a}^{a}}$ .

Now we can calculate the differentiation of above by applying the multiplication rule.

Therefore, we need to be very clear with the above discussed functions and their differentiation.

So, we need to be very clear with the basic formulas.

The common mistake is student forget to notice (Constant)function or ${{(\lambda )}^{f(x)}}$kind of function and makes mistake in correct calculation, i.e.,

$\dfrac{d}{dx}({{a}^{x}})={{a}^{x}}\ln a$

We have expression/function

\[y={{2}^{x}}-3{{e}^{x}}-{{4}^{x}}-(1)\]

Now, let us differentiate the given function as,

\[\dfrac{dy}{dx}=\dfrac{d}{dx}\left( {{2}^{x}}-3{{e}^{x}}-{{4}^{x}} \right)\]

One important rule should be applied here as stated below:

If we have $n$ functions ${{f}_{1}}(x),{{f}_{2}}(x),{{f}_{3}}(x)......{{f}_{n}}(x)$ and ${{\lambda }_{1}},{{\lambda }_{2}},{{\lambda }_{3}}......{{\lambda }_{n}}$ are constants in function $'y'$ as written below:

$y={{\lambda }_{1}}{{f}_{1}}(x)+{{\lambda }_{2}}{{f}_{2}}(x)+{{\lambda }_{3}}{{f}_{3}}(x)+......+{{\lambda }_{n}}{{f}_{n}}(x)$.

Now, if we differentiate the above given function $y$ , then we will get

$\begin{align}

& \dfrac{dy}{dx}=\dfrac{d}{dx}\left[ {{\lambda }_{1}}{{f}_{1}}(x)+{{\lambda }_{2}}{{f}_{2}}(x)+{{\lambda }_{3}}{{f}_{3}}(x)+......+{{\lambda }_{n}}{{f}_{n}}(x) \right] \\

& \dfrac{dy}{dx}=\dfrac{d}{dx}\left[ {{\lambda }_{1}}{{f}_{1}}(x) \right]+\dfrac{d}{dx}\left[ {{\lambda }_{2}}{{f}_{2}}(x) \right]+\dfrac{d}{dx}\left[ {{\lambda }_{3}}{{f}_{3}}(x) \right]+....+\dfrac{d}{dx}\left[ {{\lambda }_{n}}{{f}_{n}}(x) \right] \\

& \dfrac{dy}{dx}={{\lambda }_{1}}\dfrac{d}{dx}\left[ {{f}_{1}}(x) \right]+{{\lambda }_{2}}\dfrac{d}{dx}\left[ {{f}_{2}}(x) \right]+{{\lambda }_{3}}\dfrac{d}{dx}\left[ {{f}_{3}}(x) \right]+....+{{\lambda }_{n}}\dfrac{d}{dx}\left[ {{f}_{n}}(x) \right]........(2) \\

\end{align}$

So if functions are written in summation, then we can differentiate them individually. Using the above property in equation (1) as follows:

\[\begin{align}

& \dfrac{dy}{dx}=\dfrac{d}{dx}({{2}^{x}}-3{{e}^{x}}-{{4}^{x}}) \\

& \dfrac{d}{dx}=\dfrac{d}{dx}({{2}^{x}})-\dfrac{d}{dx}(3{{e}^{x}})-\dfrac{d}{dx}({{4}^{x}}) \\

\end{align}\]

Here, we can observe that ${{2}^{x}}$ is of type (Constant)function or ${{(\lambda )}^{f(x)}}$\ . So, we have formula for it as,

$\dfrac{d}{dx}({{a}^{x}})={{a}^{x}}\ln a$

Hence,

$\dfrac{d}{dx}({{2}^{x}})={{2}^{x}}\ln 2.........(4)$

Now, ${{e}^{x}}$ is exponential function and derivative of it is given as,

$\dfrac{d}{dx}({{e}^{x}})={{e}^{x}}........(5)$

Similarly, $\dfrac{d}{dx}({{4}^{x}})$ can be calculated by $\dfrac{d}{dx}({{a}^{x}})={{a}^{x}}\ln a$ formula as,

$\dfrac{d}{dx}({{4}^{x}})={{4}^{x}}\ln 4.........(6)$

Putting the values of equation (4), (5) and (6) in equation (3) for calculating,

\[\dfrac{dy}{dx}={{2}^{x}}\ln 2-3{{e}^{x}}-{{4}^{x}}\ln 4\]

Note: Student need to very clear with the functions like ${{a}^{x}},{{x}^{a}},{{x}^{x}},{{a}^{a}}$ .

Now we can calculate the differentiation of above by applying the multiplication rule.

Therefore, we need to be very clear with the above discussed functions and their differentiation.

So, we need to be very clear with the basic formulas.

The common mistake is student forget to notice (Constant)function or ${{(\lambda )}^{f(x)}}$kind of function and makes mistake in correct calculation, i.e.,

$\dfrac{d}{dx}({{a}^{x}})={{a}^{x}}\ln a$

Recently Updated Pages

Calculate the entropy change involved in the conversion class 11 chemistry JEE_Main

The law formulated by Dr Nernst is A First law of thermodynamics class 11 chemistry JEE_Main

For the reaction at rm0rm0rmC and normal pressure A class 11 chemistry JEE_Main

An engine operating between rm15rm0rm0rmCand rm2rm5rm0rmC class 11 chemistry JEE_Main

For the reaction rm2Clg to rmCrmlrm2rmg the signs of class 11 chemistry JEE_Main

The enthalpy change for the transition of liquid water class 11 chemistry JEE_Main

Trending doubts

Name the Largest and the Smallest Cell in the Human Body ?

Fill in the blanks A 1 lakh ten thousand B 1 million class 9 maths CBSE

Epipetalous and syngenesious stamens occur in aSolanaceae class 11 biology CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

A ball impinges directly on a similar ball at rest class 11 physics CBSE

Lysosomes are known as suicidal bags of cell why class 11 biology CBSE

Two balls are dropped from different heights at different class 11 physics CBSE

A 30 solution of H2O2 is marketed as 100 volume hydrogen class 11 chemistry JEE_Main

A sample of an ideal gas is expanded from 1dm3 to 3dm3 class 11 chemistry CBSE